1989
DOI: 10.1002/cber.19891220313
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen und Strukturen von Ethyl‐, Propyl‐, Butyl‐ und Mesitylantimon

Abstract: Die Enthalogenierung von Alkylantimondibromiden RSbBr2 (R = Et, Pr, Bu) mit Mg in THF führt zu gelben Lösungen, die überwiegend die Antimonfünfringe (RSb)5 neben den Vierringen (RSb)4 enthalten. Die Trimeren (RSb)3 können massenspektrometrisch nachgewiesen werden. Beim Entfernen des Lösungsmittels bilden sich reversibel die Polymeren (RSb)x (x » 5) in Form schwarzer Festkörper. In den Ringen nehmen die Substituenten R maximale trans‐Positionen ein. Die Kristallstruktur von (MesSb)4 · Benzol enthält linear …Sb4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Two years later the first stable diarsene with an As=As bond was synthesized , but many attempts at the isolation of stable higher homologs, distibene (RSb=SbR) and dibismuthene (RBi=BiR), were unsuccessful because of their higher tendency toward oligomerization .…”
Section: Group 15 Element Compoundsmentioning
confidence: 99%
“…Two years later the first stable diarsene with an As=As bond was synthesized , but many attempts at the isolation of stable higher homologs, distibene (RSb=SbR) and dibismuthene (RBi=BiR), were unsuccessful because of their higher tendency toward oligomerization .…”
Section: Group 15 Element Compoundsmentioning
confidence: 99%
“…(EtSb) x [2], (n-PrSb) x [2], Me 2 Sb-SbMe 2 [8], Et 2 Sb-SbMe 2 [8], (norbornadiene)Cr(CO) 4 [9], and cis-(C 5 H 11 N) 2 Mo(CO) 4 [10] were prepared as described in the literature.…”
Section: Sample Preparationmentioning
confidence: 99%
“…I nspired by the pioneering work of Rheingold [1] on the famous ladder polymer catena-(MeAs) x and on related antimony compounds, the study of the multifold chemistry of polystibanes has been in the focus of our research for many years [2][3][4][5][6]. In a preceding communication, we reported that distibanes R 2 Sb-SbR 2 (R 0 Me, Ph) react with stable antimony rings (R′Sb) n (R′ 0 Me 3 SiCH 2 , n 0 4, 5) forming of ring-chain equilibria mainly with tri-stibanes R 2 Sb-SbR′-SbR 2 [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations